Pengaruh Suku Bunga Kredit dan Dana Pihak Ketiga Terhadap Penyaluran Kredit Bank Umum Serta Dampaknya pada Pertumbuhan Ekonomi di DKI Jakarta 2014–2024 - Mutiara Izzati (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to examine the influence of the lending rate and third-party funds on commercial bank lending, as well as their impact on economic growth in DKI Jakarta during the 2014-2024 period. The research method employs a quantitative approach using quarterly time-series secondary data (44 observations), analysed via multiple linear regression and simple linear regression using the Indicator Saturation (IIS) approach to handle extreme outliers. The test results show that the Loan Interest Rate has a negative and significant effect, while Third-Party Funds have a positive and significant effect on credit disbursement. However, further findings reveal an empirical anomaly that contradicts classical theory: an increase in credit disbursement actually has a negative and significant effect on regional economic growth. This negative relationship is caused by the phenomenon of credit misallocation loans are absorbed more for consumption and short-term liquidity due to the shocks of the COVID-19 pandemic, rather than for productive investment. In conclusion, interest rates and public deposits are key determinants of the volume of bank credit, but the success of financial intermediation in driving the economy depends not only on the quantity of funds but is largely determined by their quality, the appropriateness of their allocation, and the productivity of their use in the real sector.